Oral Presentations Abstracts: MORAL OR ETHICAL EXPERTS? THE ROLE OF BIOETHICISTS IN A DEMOCRATIC SOCIETY - ŁUKÓW, Paweł (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 It is often believed that if bioethicists are to play the role of experts, the nature of their expertise must be explained and the authority of their advice justified. This presentation will be a moderate challenge to this view. It will be contended that the nature of bioethical expertise and the source of bioethicists’ authority depends on the kind of advice that is expected from them. If one expects a moral advice, i.e. a self-standing instruction about what to do in a given situation, it is indeed hardly possible to identify a moral expert in a rational way, and so to take their advice as authoritative. If, however, the counsel sought is to be an ethical advice, that is, a recommendation guided by a particular normative context, bioethicists can be sufficiently good experts and their instructions can enjoy a significant authority. Since bioethics is a field of research and social practice which developed in a democratic society, the bioethicist’s advice presupposes the normative framework of the values and ideals of democracy such as mutual recognition and respect, liberty and equality. Accordingly, although a bioethicist is not to be expected to be a moral expert (this role belongs, for example, to spiritual or religious leaders), she can be an ethical expert, who – on the ground of her knowledge of the values and ideals of a democratic society, ethical theory and, among other things, social theory and law – can offer a reliable advice which addresses a particular problem. The expert status of a bioethicist and the authority of her advice derives crucially from the values and ideals of a democratic society and her ethical knowledge, rather than from a moral insight into a realm of context-independent values.